The Development of Reading Materials in School Literacy Movements for Senior High School Students Based on Local Culture of Karo - Yoana Stephani Tarigan; Biner Ambarita; Mutsyuhito Solin (BIRCU, 2019)
Literacy has the meaning and implications of basic reading and writing skills to acquire and manipulate knowledge through written texts, from metalinguistic analysis of grammatical units to the structure of oral and written texts. This study deals with the development of reading materials in school literacy movements for senior high school students based on local culture of Karo. The type of this study is development study that is the development of short story text reading materials based on character education as an ingredient in the school literacy movement. This development study refers to the development theory proposed by Borg and Gall. The conclusion of this study is the feasibility of reading material in the school literacy movement for senior high school students based on local culture of Karo is eligible and suitable to be used as reading material, based on the assessment of material experts, and design experts. The results of the assessment based on the responses of teachers and students in the Senior High School 1 of Berastagi concluded that reading material in the school literacy movement for senior high school students based on local culture of Karo had been found to be effective because it met the needs and overall criteria